Preparation method of bifunctional magnetic Fe3O4 (at) MXene (at) Ag NPs with SERS (Surface Enhanced Raman Scattering) and photo-Fenton catalytic activity and application of bifunctional magnetic Fe3O4 (at) MXene (at) Ag NPs in wastewater treatment

By loading Fe3O4 and Ag NPs on 2D MXene, the dual-functional magnetic nanosheets prepared by Fe3O4@MXene@Ag NPs were solved, and the problem of organic pollutants detection and removal in wastewater was achieved, high sensitivity detection and efficient degradation were achieved, and reusable and magnetic recovery was supported.

CN119869577APending Publication Date: 2025-04-25LIAONING UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510076921.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

It is difficult for the prior art to achieve high sensitivity detection and effective removal of organic pollutants in wastewater at the same time, and traditional water treatment technologies usually require different materials and processes, which are difficult to meet environmental management needs.

Method used

A dual-functional magnetic nanosheet Fe3O4@MXene@Ag NPs was developed. Through coprecipitation and electrostatic self-assembly technology, Fe3O4 and Ag NPs were loaded on 2D MXene to achieve SERS detection and photofenton catalytic degradation.

Benefits of technology

It realizes ultra-sensitive detection and efficient degradation of organic pollutants in sewage, has good repeatability and magnetic recovery, supports the "detection and then removal" treatment process, and significantly improves the efficiency and effect of the water treatment process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869577A_ABST
    Figure CN119869577A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of sewage treatment, and particularly relates to a preparation method of difunctional magnetic Fe3O4 (at) MXene (at) Ag NPs with SERS and photo-Fenton catalytic activity and application of the difunctional magnetic Fe3O4 (at) MXene (at) Ag NPs to trace detection and photo-Fenton degradation of organic pollutants in sewage. The preparation method comprises the following steps: firstly, etching an aluminum atom layer of a Ti3AlC2MAX phase by using an acidic etching solution, then carrying out a layering process to synthesize 2D MXene, and loading the 2D MXene on Fe3O4 and Ag NPs by adopting coprecipitation and electrostatic adsorption to prepare the difunctional magnetic Fe3O4 (at) MXene (at) Ag NPs composite material with SERS (Surface Enhanced Raman Scattering) and photo-Fenton catalytic activity. The detection limit of the composite material SERS substrate to crystal violet (CV) is as low as 1.08 * 10 <-12 > M, and the degradation rate of CV within 40 min reaches 91.5% under visible light irradiation and Fenton effect. The magnetic property of the composite material is also convenient to recycle and reuse, excellent SERS sensitivity can be kept even after 8 times of circulation, relatively strong photocatalytic performance can be kept even after 3 times of circulation, and the composite material is a very promising wastewater treatment material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sewage treatment, and specifically relates to a preparation method of bifunctional magnetic Fe3O4@MXene@Ag NPs with SERS and photo-Fenton catalytic activity and application of the same in trace detection and photo-Fenton degradation of organic pollutants in sewage. Background Art

[0002] Water pollution remains a serious problem today, greatly exacerbated by industrial and urban development. Emissions of organic pollutants, especially dyes from industries such as textiles and printing, are a significant contributor to the problem. The properties of various dyes pose a significant threat to water integrity and aquatic life, ultimately endangering ecological balance and human health. Therefore, the detection and removal of organic dyes from polluted waters is essential to protect public health and promote ecological restoration.

[0003] Surface enhanced Raman scattering (SERS) technology is considered a promising method for ultrasensitive environmental pollutant analysis as a simple, rapid, economical and effective method. Trace detection of organic pollutants using SERS has attracted increasing research attention. While the detection of organic pollutants in polluted water is essential, the effective removal of these pollutants poses additional challenges to wastewater treatment. To purify water quality, various traditional water treatment technologies have been explored, including adsorption, advanced oxidation processes (AOPs), flocculation, nanofiltration, phytoremediation, precipitation, reverse osmosis membranes, etc. Among them, the photo-Fenton process produces highly oxidative ·OH radicals in the presence of Fe elements. This process can rapidly and non-selectively oxidize tough macromolecular organic matter in wastewater into smaller and more degradable molecules, or directly mineralize them into carbon dioxide and water. Although these technologies are quite mature, they usually require different materials to achieve different functions. However, ideally, the treatment of pollutants in water follows a sequential reaction of analysis and removal, making single-functional approaches increasingly unable to meet the escalating environmental management needs. Therefore, composite materials that can first detect and then degrade pollutants are becoming attractive candidates for environmental remediation and water treatment.

[0004] 2D MXene-based materials have attracted great attention due to their large specific surface area, excellent electrical conductivity, high hydrophilicity, and numerous active sites, making them suitable for organic pollutant adsorption, SERS, and Fenton-like reactions for pollutant detection and removal. Despite the promising prospects, the practical application of MXene is often limited by challenges related to recycling. To address this issue, magnetic MXene has emerged as a promising alternative because their strong magnetic properties can be easily separated from the reaction medium using an external magnetic field, thereby enabling reuse and improving the sustainability of environmental applications. Fe3O4 is known for its excellent magnetic properties, recyclability, and catalytic activity, and has been widely used as a photo-Fenton catalyst and pollutant adsorbent. In addition, Ti3C2T X The Ti component in the MXene introduces strong reducing properties, which can improve the Fe(III) / Fe(II) cycle, accelerate electron transfer, and activate H2O2, which together increase the generation of reactive oxygen species (ROS) and improve the photo-Fenton degradation efficiency. In addition, the deposition of Ag nanostructures on the MXene surface introduces the localized surface plasmon resonance (LSPR) effect, which enhances light absorption and improves the separation of photogenerated electron-hole pairs, thereby significantly improving the photocatalytic activity. This multifunctional composite approach provides a recyclable and efficient catalytic system for sustainable removal of pollutants and holds great promise in future environmental applications.

[0005] Previous studies have shown that the excellent conductivity of MXene improves SERS efficiency by promoting efficient charge transfer (CT), which is consistent with the chemical mechanism (CM) of SERS enhancement. By modifying the MXene surface with noble metals (such as Au or Ag) to form a nanolayered metal structure, the electromagnetic field distribution can be significantly enhanced, thereby further improving the SERS sensitivity. In addition, the unique band structure of MXene contributes to the effective dispersion of photoinduced charges between analytes and semiconductor / metal composites, providing synergistic SERS enhancement. In view of these advantages, the development of magnetic SERS substrates by coupling MXene with magnetic and noble metal nanoparticles has important prospects. Such composites combine high SERS activity with excellent separation and enrichment capabilities, thereby achieving fast and efficient detection.

[0006] Inspired by the above ideas, we developed a bifunctional Fe3O4@MXene@Ag NPs nanocomposite that combines ultrasensitive SERS sensing with efficient photo-Fenton catalytic activity. Through co-precipitation and electrostatic self-assembly techniques, we successfully created a bifunctional substrate that can detect organic pollutants in water and promote their photocatalytic degradation. Crystal violet (CV) was selected as a reporter molecule to evaluate the SERS activity, and the finite-difference time-domain (FDTD) algorithm was used to simulate the "hot spot" distribution to understand the SERS enhancement mechanism. In addition, the photo-Fenton performance of Fe3O4@MXene@Ag NPs for CV degradation was studied and the relevant mechanism was proposed. The results show that the addition of Ag NPs significantly improves the separation efficiency of photogenerated electron-hole pairs, thereby enhancing the photo-Fenton activity. In addition, the magnetic Fe3O4 nanocrystals can easily recover the composite using a magnet, allowing its reuse in SERS detection and photo-Fenton degradation of CV. This study not only advances the understanding of SERS and photo-Fenton mechanisms in dual-functional sensors, but also opens new avenues for designing efficient and recyclable hybrid sensors for the detection and degradation of organic pollutants at a scalable production level. Summary of the invention

[0007] This paper designs a method to load 2D MXene with Fe3O4 and Ag NPs by coprecipitation and electrostatic adsorption, successfully prepares a bifunctional magnetic nanosheet, and characterizes its structure, detection mechanism and SERS performance. In addition, its photo-Fenton degradation performance and degradation mechanism are studied. The specific research contents are as follows:

[0008] (1) The present invention uses coprecipitation and electrostatic adsorption to load Fe3O4 and Ag NPs on 2D MXene to prepare bifunctional magnetic nanosheets, and uses TEM, SEM, XPS, UV-visible absorption spectroscopy, FT-IR, and VSM to characterize its surface properties, morphology, and structure. The experimental results show that the bifunctional magnetic nanosheets Fe3O4@MXene@AgNPs were successfully synthesized and can be used for trace detection and removal of organic pollutants in sewage.

[0009] (2) The bifunctional magnetic nanosheets Fe3O4@MXene@AgNPs provided by the present invention can be used as an efficient SERS substrate for the detection of organic pollutants. The experimental results show that MXene has excellent electrical conductivity and can promote effective charge transfer (CT), thereby significantly improving the SERS enhancement effect. The material achieves ultra-sensitive detection of organic pollutants through a synergistic enhancement mechanism of physics and chemistry.

[0010] (3) The bifunctional magnetic nanosheets Fe3O4@MXene@AgNPs provided by the present invention can be used as photo-Fenton catalysts for photo-Fenton degradation of organic pollutants. X The Ti component in MXene introduces strong reducing properties, which can improve the Fe(III) / Fe(II) cycle, accelerate electron transfer, activate H2O2, and together increase the generation of reactive oxygen species (ROS), improving the photo-Fenton degradation efficiency. In addition, the deposition of Ag nanostructures on the MXene surface introduces the localized surface plasmon resonance (LSPR) effect, which enhances light absorption and improves the separation of photogenerated electron-hole pairs, thereby significantly improving the photocatalytic activity.

[0011] (4) The dual-functional material provided by the present invention has magnetic properties, so that the material can be quickly enriched and recovered, reducing secondary pollution, and can be used for material recycling. The uniformity, stability and repeatability of the material were investigated. The results show that Fe3O4@MXene@AgNPs has acceptable uniformity, and the SERS intensity has almost no change within 30 days, and has good repeatability.

[0012] (5) The Fe3O4@MXene@Ag NPs proposed in this invention are an innovative dual-functional material with excellent SERS activity and photo-Fenton degradation ability for pollutants. The composite material supports the sequential "detection then removal" treatment process of wastewater, promotes effective pollutant removal, and helps to alleviate environmental pollution. This paper investigates the SERS detection and photo-Fenton degradation effects of organic pollutants in three actual water samples. The results show that Fe3O4@MXene@Ag NPs not only achieves high-sensitivity detection of pollutants, but also further purifies water through photo-Fenton degradation, significantly improving the efficiency and effectiveness of the water treatment process.

[0013] The present invention uses hydrochloric acid and lithium fluoride to etch MAX to obtain accordion-shaped MXene, and further obtains MXene nanosheets by DMSO stripping; then magnetic Fe3O4 is loaded on the MXene nanosheets by coprecipitation; then positively charged Ag NPs are further loaded on the magnetic nanosheets by electrostatic adsorption to obtain bifunctional magnetic nanosheets. The magnetic nanosheets not only have good SERS performance, but also have good photo-Fenton degradation performance, so it is expected to realize trace detection and removal of organic pollutants in sewage.

[0014] The specific technical solutions are as follows:

[0015] A method for preparing bifunctional magnetic Fe3O4@MXene@Ag NPs with SERS and photo-Fenton catalytic activity comprises the following steps:

[0016] 1) 100 mL of FeCl3·6H2O aqueous solution and 100 mL of FeCl2·4H2O aqueous solution were placed in a beaker, 1 mg / mL of MXene dispersion was added, and the mixture was stirred for 6 h. Then, 3 M NaOH solution was added to adjust the pH. The synthesis was continued for 2 h under mechanical stirring. A magnet was placed outside the beaker to make the nanosheets close to the inner surface of the beaker. The supernatant liquid was removed by pouring. Then, ethanol was added as a dispersant to the residual nanosheets, and the nanosheets were dispersed by oscillation. Then, the nanosheets were collected by magnetism and washed three times with ethanol to obtain Fe3O4@MXene nanosheets.

[0017] 2) The Fe3O4@MXene nanosheets were dispersed in 5 mL of ethanol and ultrasonically treated for 20 min, then the Ag NPs solution was added and further ultrasonically treated for 4 h to ensure that the Ag NPs were loaded on the Fe3O4@MXene. Subsequently, the excess AgNPs were removed by washing with water and ethanol, and the product was dried to obtain Fe3O4@MXene@Ag NPs.

[0018] Furthermore, in the above-mentioned method for preparing Fe3O4@MXene@Ag NPs, in step 1), the concentration of the FeCl3·6H2O aqueous solution is 0.030 mol / L, and the concentration of the FeCl2·4H2O aqueous solution is 0.015 mol / L.

[0019] Furthermore, in the above-mentioned method for preparing Fe3O4@MXene@Ag NPs, in step 1), the pH is adjusted to 12.

[0020] Furthermore, in the above-mentioned method for preparing Fe3O4@MXene@Ag NPs, in step 2), the amount of the Fe3O4@MXene nanosheets used is 0.05 g, and the amount of the Ag NPs solution used is 20 mL.

[0021] Furthermore, in the above-mentioned method for preparing Fe3O4@MXene@Ag NPs, in step 1), the method for preparing the MXene dispersion comprises the following steps:

[0022] 1) LiF was gradually added to the hydrochloric acid solution and stirred vigorously until the mixture changed from milky white to a transparent solution to form an acidic etching solution. Subsequently, Ti3AlC2 MAX phase powder was gradually added and stirred continuously at 35°C for 24 hours. After the reaction was completed, deionized water was added and centrifuged at 5000 rpm for 8 minutes. The supernatant was discarded and the deionized water washing and centrifugation cycle was repeated until the pH of the supernatant was close to 7. The black paste produced by centrifugation was freeze-dried to produce multilayer MXene nanosheets.

[0023] 2) The multilayer MXene nanosheets were dispersed in DMSO and stirred continuously at 35 °C for 24 h. The mixture was then centrifuged at 8000 rpm for 5 min to remove DMSO. The remaining black paste was redispersed in 200 mL of deionized water and ultrasonically treated for 12 h to obtain a MXene dispersion with a concentration of 1 mg / mL.

[0024] Furthermore, in the above-mentioned method for preparing the MXene dispersion, in step 1), 1.6 g of LiF is gradually added to 20 mL of 9 M hydrochloric acid solution.

[0025] Furthermore, in the above-mentioned method for preparing the MXene dispersion, in step 1), the amount of Ti3AlC2 MAX phase powder added is 1 g.

[0026] Furthermore, in the above-mentioned method for preparing the MXene dispersion, in step 2), 0.2 g of multilayer MXene nanosheets is dispersed in 20 mL of DMSO.

[0027] Furthermore, in the above-mentioned method for preparing Fe3O4@MXene@Ag NPs, in step 2), the method for preparing the Ag NPs solution comprises the following steps:

[0028] 1) Prepare solution A and solution B: solution A is 100 mL of an aqueous solution containing 2 mM AgNO3, 0.4 M NH3OH and 0.5 mM CTAB, and solution B is 100 mL of an aqueous solution containing 8 mM NaBH4 and 0.5 mM CTAB;

[0029] 2) Place solution A and solution B in an ice bath and cool for 10 minutes. Under vigorous stirring, drop solution B into solution A in the ice bath. Within 2 minutes, the solution turns yellow. Continue stirring in the dark for 3 hours. Subsequently, the particle dispersion is rapidly boiled, refluxed for 10 minutes, and then cooled to room temperature.

[0030] The application of bifunctional magnetic Fe3O4@MXene@Ag NPs with SERS and photo-Fenton catalytic activity prepared by any of the preparation methods described above in trace detection and photo-Fenton degradation of organic pollutants in sewage.

[0031] The beneficial effects of the present invention are:

[0032] 1. The present invention adopts the synergistic enhancement mechanism of EM and CT to achieve ultra-sensitive detection of crystal violet, an organic pollutant in sewage, with a detection limit as low as 1.08×10 -12 M. Thus, a highly sensitive SERS substrate was prepared, which has potential application value in the detection of organic pollutants in sewage.

[0033] 2. The bifunctional magnetic nanosheets prepared by the present invention exhibit good SERS performance, stability and recyclability, providing a new strategy for the actual detection of organic pollution in sewage.

[0034] 3. The present invention has significant dye degradation ability based on the excellent photo-Fenton catalytic activity of Fe3O4. Under visible light irradiation and Fenton effect, the degradation rate of CV within 40 minutes reaches 91.5%.

[0035] 4. Based on the excellent recyclability and catalytic activity of Fe3O4, the present invention makes the bifunctional nanosheets easy to recycle and reuse, and can maintain excellent SERS sensitivity even after 8 cycles, and can maintain strong photo-Fenton catalytic degradation performance after 3 cycles.

[0036] 5. The bifunctional magnetic nanosheets Fe3O4@MXene@Ag NPs prepared in the present invention show recognition and high sensitivity in detecting organic pollutants, as well as efficient degradation ability, making it a very promising wastewater treatment material. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 (A) is the UV-visible absorption spectrum of Ag NPs in Example 1, and the inset is a digital photo of Ag NPs; (B) is the TEM image of Ag NPs, and the inset is a high-resolution TEM image of Ag NPs.

[0038] Figure 2 These are SEM images of Ti3AlC2 (MAX phase) before (A) and after (B) acid etching in Example 1, and (C) is a photograph of two-dimensional layered MXene.

[0039] Figure 3 are typical SEM (A) and TEM (B) images of MXene in Example 1, (C) is the SEM image of Fe3O4@MXene composite material, (D) is the SEM image of Fe3O4@MXene@Ag NPs composite material, and (E) is the elemental mapping corresponding to Fe3O4@MXene@Ag NPs.

[0040] Figure 4(A) is the FT-IR spectra of Fe3O4, MXene and Fe3O4@MXene in Example 1, (B) is the XRD spectra of MAX and MXene, (C) is the XRD spectra of Fe3O4@MXene and Fe3O4@MXene@Ag NPs, (D) is the XPS spectra of MXene, Fe3O4@MXene and Fe3O4@MXene@Ag NPs, (E) is the Ag three-dimensional nuclear energy level spectrum of Fe3O4@MXene@AgNPs, (F) is the hysteresis curves of Fe3O4 and Fe3O4@MXene@Ag NPs and a photograph of the magnetic separation behavior of Fe3O4@MXene@Ag NPs in solution.

[0041] Figure 5 (A) is the 10 nanoparticles collected on MXene, Ag NPs, Fe3O4@MXene, and Fe3O4@MXene@Ag NPs in Example 2. -5 M CV power Raman and SERS spectra, (B) CV collected on MXene (a), Fe3O4@MXene (b), Ag NPs (c), Fe3O4@MXene@Ag NPs (d) at 1617 cm -1 (C) is the proposed dual enhancement mechanism of the Fe3O4@MXene@Ag NPs composite substrate, (D) is the energy level diagram describing the CT process between the Fe3O4@MXene@Ag NPs composite substrate and CV, and (E) is the E field distribution diagram of the finite difference time domain (FDTD) simulation of MXene (left), Ag NPs (middle) and MXene@Ag NPs (right) substrates.

[0042] Figure 6 (A) is the different concentrations (1×10 -5 ~1×10 -11 M) SERS spectrum of CV on SERS substrate, (B) based on 1617 cm -1 Calibration curves [CV] of Raman intensity vs Log C, the error bars represent the standard deviation determined by 3 independent measurements, (C) is a comparison of the linear range and LOD of CV detection of Fe3O4@MXene@Ag NPs with other materials.

[0043] Figure 7 (A) is the SERS spectra of a set of 10 μM CV solutions obtained from 20 random positions in Example 2, and (B) is the SERS spectra of 1617 cm -1 (C) is the Raman intensity at 10 μM CV detected by Fe3O4@MXene@AgNPs, and (D) is the quantitative result of CV SERS intensity in (C).

[0044] Figure 8 : This is the photo-Fenton degradation (A) and reaction kinetics diagram (B) of CV on different samples in Example 3; this is the CV degradation (C) and reaction kinetics diagram (D) of Fe3O4@MXene@Ag NPs under different conditions, experimental conditions: [CV]0=10μM, [catalyst]=250mg / L, [H2O2]=5mM, pH (unadjusted).

[0045] Fig. 9 (A) is the UV-visible spectra (DRS) and band gap energy (B) of Fe3O4, Fe3O4@MXene and Fe3O4@MXene@Ag NPs in Example 3; (C) is the EIS graph of Fe3O4@MXene and Fe3O4@MXene@Ag NPs.

[0046] Fig.10 The effect of different scavengers on the CV removal efficiency of Fe3O4@MXene@Ag NPs in Example 3 (A), TEMPO-h + (B), DMPO-·O 2- (C) and ESR spectra of DMPO-·OH (D).

[0047] Fig.11 The Fe3O4@MXene@Ag NPs in Example 4 were 10 -5 M CVSERS spectrum (A) and 1617 cm -1 (B) The peak intensity at 1617 cm-1 of Fe3O4@MXene@Ag NPs during 8 photo-Fenton system cycles. (C) The cyclic SERS detection of CV and R6G with different concentrations of dyes. (D) The CV of Fe3O4@MXene@Ag NPs during 8 photo-Fenton system cycles. -1 and R6G at 1648cm -1 The SERS intensity at .

[0048] Fig.12 (A) is the degradation of Fe3O4@MXene@Ag NPs to CV in three cycles in Example 4, (B) is the hysteresis loop of Fe3O4@MXene@Ag NPs measured at room temperature, (C) is the XPS spectra of fresh and used Fe3O4@MXene@Ag NPs catalysts, (D) is the Fe 2p high-resolution XPS spectra of fresh and used Fe3O4@MXene@Ag NPs catalysts, and (E) is the XRD spectra of fresh and used Fe3O4@MXene@Ag NPs catalysts.

[0049] Fig.13(A) is the geographical distribution and image of the sampling points in Example 5, (B) is a schematic diagram of the sequential detection and cyclic detection process, and (C) is a schematic diagram of the dual-functional material at 10 -5 Sequential treatment of simulated wastewater under M CV, showing the stepwise process of adsorption, detection, and degradation, followed by recovery and reuse of materials.

[0050] Fig.14 The preparation process of the bifunctional magnetic Fe3O4@MXene@Ag NPs composite substrate is shown, and the corresponding CV is analyzed and the schematic diagram of degradation is shown. DETAILED DESCRIPTION

[0051] In order to better understand the technical solution of the present invention, specific embodiments are further described in detail, but the technical solution is not limited thereto.

[0052] Example 1 Preparation method of dual-functional nanosheets Fe3O4@MXene@Ag NPs

[0053] 1) Synthesis of Ag NPs

[0054] Solution A and solution B were prepared: Solution A was a 100 mL aqueous solution containing 2 mM AgNO3, 0.4 M NH3OH and 0.5 mM CTAB, and solution B was a 100 mL aqueous solution containing 8 mM NaBH4 and 0.5 mM CTAB. The two solutions were then placed in an ice bath to cool for 10 minutes. Under vigorous stirring, solution B was dropped into solution A in the ice bath. Within 2 minutes, the solution turned yellow, indicating the formation of AgNPs. Stirring was continued in the dark for 3 hours. Subsequently, the particle dispersion was quickly boiled, refluxed for 10 minutes, and then cooled to room temperature.

[0055] 2) Preparation of two-dimensional layered MXene

[0056] The synthesis of two-dimensional layered MXene is achieved by first etching the aluminum atomic layer of the Ti3AlC2 MAX phase using an acidic etching solution and then performing a layering process. First, 1.6 g of LiF was gradually added to 20 mL of 9 M hydrochloric acid solution and stirred vigorously until the mixture changed from milky white to a transparent solution to form an acidic etching solution. Subsequently, 1 g of Ti3AlC2 MAX phase powder was gradually added and stirred continuously at 35 ° C for 24 h. After the reaction was completed, deionized water was added, centrifuged at 5000 rpm for 8 min, the supernatant was discarded, and the deionized water washing centrifugation cycle was repeated until the supernatant pH was close to 7. The black paste produced by centrifugation was then freeze-dried to produce multilayer MXene nanosheets. To further form two-dimensional layered MXene, 0.2 g of multilayer MXene nanosheets were dispersed in 20 mL of DMSO using the DMSO intercalation method and stirred continuously at 35 ° C for 24 h. The mixture was then centrifuged at 8000 rpm for 5 minutes to remove DMSO. The remaining black paste was redispersed in 200 mL of deionized water and sonicated for 12 h to obtain a MXene dispersion with a concentration of 1 mg / mL.

[0057] 3) Preparation of Fe3O4@MXene

[0058] 100 mL of FeCl3·6H2O aqueous solution (0.030 mol / L) and FeCl2·4H2O aqueous solution (0.015 mol / L) were placed in a beaker, 1 mg / mL of MXene dispersion was added, and the mixture was stirred for 6 h, and then 3 M NaOH solution was added until the pH reached 12. The synthesis was continued for 2 h under mechanical stirring. A magnet was placed outside the beaker to make the nanosheets close to the inner surface of the beaker, and the supernatant liquid was removed by pouring, and then ethanol was added as a dispersant to the remaining nanosheets, and the nanosheets were dispersed by oscillation, and then the nanosheets were collected by magnetism and washed three times with ethanol to obtain Fe3O4@MXene nanosheets.

[0059] 4) Preparation of Fe3O4@MXene@Ag NPs

[0060] The synthesized 0.05 g Fe3O4@MXene nanosheets were dispersed in 5 mL ethanol and sonicated for 20 min, then 20 mL Ag NPs solution was added and further sonicated for 4 h to ensure that the Ag NPs were loaded on Fe3O4@MXene. Subsequently, the excess Ag NPs were removed by washing with water and ethanol. The product was then dried to obtain Fe3O4@MXene@Ag NPs.

[0061] The composition and properties of related materials are shown in Figure 1 , Figure 2 , Figure 3 and Figure 4 .

[0062] Figure 1 (A) is the UV-visible absorption spectrum of Ag NPs in Example 1, and the inset is a digital photo of Ag NPs; (B) is the TEM image of Ag NPs, and the inset is a high-resolution TEM image of Ag NPs.

[0063] Figure 1 (A) is the UV-visible absorption spectrum of Ag NPs, and the inset is a digital photo of Ag NPs. The synthesized Ag NPs colloidal solution is transparent and bright yellow, indicating that the Ag NPs are well dispersed in the aqueous medium. The characteristic plasmon absorption peak of Ag NPs was observed at 399nm, with a sharp and narrow full width at half maximum, confirming the uniform size distribution and stability of Ag NPs in solution, and no aggregation or alteration was detected. Figure 1 (B) is a TEM image of Ag NPs, and the inset is a high-resolution TEM image of Ag NPs. The morphology and size distribution of Ag NPs were further characterized by TEM. The particles were spherical with an average diameter of about 20 nm, which is consistent with the results of UV-visible spectroscopy. In the high-resolution TEM image, the lattice fringes of the silver nanoparticles are Figure 1 (B) The measured interplanar spacing is 0.145 nm, corresponding to the (220) plane of face-centered cubic (FCC) Ag, further confirming the crystallinity of the synthesized nanoparticles.

[0064] like Figure 2 The SEM images of Ti3AlC2 (MAX phase) before (A) and after (B) acid etching, and (C) a photo of two-dimensional layered MXene. Ti3AlC2 (MAX phase) presents a block structure. After acid etching, obvious multilayer accordion-like Ti3C2T X structure, indicating that the Al layer in the Ti3AlC2 MAX phase was successfully removed.

[0065] Figure 3 are typical SEM (A) and TEM (B) images of MXene in Example 1, (C) is the SEM image of Fe3O4@MXene composite material, (D) is the SEM image of Fe3O4@MXene@Ag NPs composite material, and (E) is the elemental mapping corresponding to Fe3O4@MXene@Ag NPs.

[0066] like Figure 3The following are typical SEM (A) and TEM (B) images of MXene, (C) is the SEM image of Fe3O4@MXene composite, (D) is the SEM image of Fe3O4@MXene@Ag NPs composite, and (E) is the corresponding elemental mapping of Fe3O4@MXene@Ag NPs. After DMSO treatment, this accordion-like structure is transformed into stacked monolayer nanosheets. TEM further confirms the formation of relatively wide monolayer MXene sheets. The exfoliation of two-dimensional layered MXene flakes can be achieved by DMSO-assisted ultrasound, which may create additional nucleation sites for the growth of Fe3O4 and Ag NPs. The SEM image of Fe3O4@MXene shows that the material retains the two-dimensional layered structure of MXene. Fe3O4 nanoparticles are dispersed on the surface, increasing the surface roughness. It can also be observed that smaller Fe3O4 particles are prone to aggregate and form irregular clusters. This is mainly attributed to the van der Waals force between Fe3O4 nanoparticles, which may lead to the adsorption and cross-linking of surface functional groups. These findings confirm the successful preparation of Fe3O4@MXene. In addition, when positively charged Ag NPs are mixed with negatively charged Fe3O4@MXene particles, the surface charge of Fe3O4@MXene shifts toward lower values. However, in the synthesized Fe3O4@MXene@AgNPs, the Fe3O4 and MXene flake structures remain intact, indicating that the electrostatic adsorption process does not destroy the MXene flake structure. In addition, it is obvious that more spherical particles are anchored on the MXene surface, leaving few empty spots, indicating that Ag NPs are successfully loaded on the MXene flakes. To further confirm the successful loading of Ag NPs on Fe3O4@MXene, energy dispersive spectroscopy (EDS) measurements were performed. The corresponding EDS elemental map shows that C, O, Ti, F, Fe, and Ag are uniformly distributed on the surface of the composite, indicating that Fe3O4 and Ag NPs are well distributed on the MXene flakes.

[0067] like Figure 4(A) is the FT-IR spectra of Fe3O4, MXene and Fe3O4@MXene, (B) is the XRD spectra of MAX and MXene, (C) is the XRD spectra of Fe3O4@MXene and Fe3O4@MXene@Ag NPs, (D) is the XPS spectra of MXene, Fe3O4@MXene and Fe3O4@MXene@Ag NPs, (E) is the Ag three-dimensional nuclear energy level spectrum of Fe3O4@MXene@Ag NPs, (F) is the hysteresis curves of Fe3O4 and Fe3O4@MXene@Ag NPs, and the magnetic separation behavior photos of Fe3O4@MXene@Ag NPs in solution. FT-IR spectra of material samples highlight the presence of characteristic functional groups. Although the overall trends of each material are similar, the intensities of specific absorption bands are different. Compared with the FT-IR spectrum of pure MXene, the Fe3O4@MXene composite has a strong absorption band at 3426cm -1 and 1426cm -1 (corresponding to -OH group), 1626 cm -1 (C=O) and 623cm -1 The absorption at (Ti-O) is significantly stronger. This indicates that the iron ions are effectively incorporated into the MXene structure, which may activate the otherwise inactive functional groups in the Fe3O4@MXene composite.

[0068] The X-ray diffraction (XRD) spectra of the material samples clearly show the obvious diffraction peaks corresponding to the Ti3AlC2 MAX phase crystals. However, after acid etching and subsequent ultrasonic-assisted DMSO stripping, the characteristic peaks of Ti3AlC2, especially the (104) peak at 38.7°, are significantly reduced. The (002) diffraction peak moves from 2θ = 9.52° to 2θ = 7.48°, indicating that the Al layer is selectively etched, causing the Ti3AlC2 phase to transform into MXene flakes. Figure 4C is the XRD pattern of the dual-functional material. The diffraction peaks at 30.1°, 35.4°, 43.1°, 56.9° and 62.6° correspond to the (220), (311), (400), (333) and (440) crystal planes of Fe3O4 (JCPDS No.74-0748), respectively. It is worth noting that the Fe3O4@MXene composite material retains the characteristic peaks of Fe3O4, indicating that its crystal form and phase remain intact. The lower intensity of some MXene peaks in the Fe3O4@MXene structure may be due to the coverage of Fe3O4, which reduces the crystallinity of the substrate, further confirming the formation of Fe3O4 on the MXene surface. In addition, after AgNPs were loaded onto Fe3O4@MXene by electrostatic adsorption, additional diffraction peaks appeared at 38.0°, 44.3°, 64.4°, and 77.2°, corresponding to the (111), (200), (220), and (311) planes of metallic Ag, JCPDS No. 04-0783. These data confirm that silver nanoparticles are deposited on the surface of Fe3O4@MXene, which is consistent with the results of SEM and EDS analysis.

[0069] The full XPS spectrum provides important information. Specifically, the synthesized MXene is mainly composed of Ti, O, C and F elements. Notably, the XPS spectrum shows binding energy peaks at 284.08 eV, 459.08 eV, 528.08 eV and 685.08 eV, corresponding to C1s, Ti 2p, O 1s and F1s states, respectively. After further co-precipitation, three new peaks at 712.08 eV and 724.08 eV appeared in the spectrum compared with Fe3O4@MXene, which are Fe(II)2p 3 / 2 and Fe(II)2p1 / 2, respectively. In addition, after Ag NPs were loaded onto the Fe3O4@MXene surface by electrostatic adsorption, the characteristic peak of Ag 3d was observed at 367.08 eV. XPS analysis of the valence state and electronic structure of the elements confirmed the successful deposition of Fe3O4 and Ag NPs. Ag 3d 5 / 2 (368.08 eV) and Ag3d 3 / 2 The double peak binding energy of (374.08 eV) is as follows Figure 4 As shown in E, it is confirmed that Ag 0 , indicating the successful synthesis of Fe3O4@MXene@Ag NPs.

[0070] The presence of Fe3O4 makes the composite material magnetic, which is beneficial for the recovery of the material from the solution. The hysteresis loops of the Fe3O4 precursor and the Fe3O4@MXene@Ag NPs hybrid were measured at room temperature using a vibrating sample magnetometer. The results show that the synthesized material has typical superparamagnetism, and the remanence and coercivity are close to zero. Among them, the saturation magnetization values ​​of Fe3O4 and Fe3O4@MXene@Ag NPs are 49.56emu·g -1 and 39.61emu·g -1 The reduced magnetization of Fe3O4@MXene@Ag NPs compared to pure Fe3O4 is due to the combination with nonmagnetic materials. Figure 4 As shown in Figure F, Fe3O4@MXene@Ag NPs can be quickly separated from the dispersed solution by an external magnetic field, showing sufficient magnetic behavior. In practical applications, this property is crucial to reduce catalyst loss and prevent secondary contamination.

[0071] Example 2 Sensing mechanism of bifunctional nanosheets Fe3O4@MXene@Ag NPs as SERS sensor

[0072] 1) SERS detection

[0073] CV and R6G were selected as cationic probe molecules for SERS studies. Solutions of these molecules at different concentrations were prepared with distilled water. Subsequently, 1 mL of each probe molecule solution was added to 1 mg of Fe3O4@MXene@Ag NPs. The mixture was then allowed to absorb onto the surface for 1 h in the dark. Subsequently, the Fe3O4@MXene@Ag NPs were magnetically collected and a 5 μL droplet of the enriched solution was placed on a glass substrate. Raman measurements were performed after the water was evaporated at room temperature.

[0074] 2) Finite Difference Time Domain Simulation (FDTD)

[0075] FDTD simulation verifies the existence of three-dimensional (3D) electromagnetic "hot spots". The incident light has a wavelength of 532nm, is oriented along the z-axis, and is polarized perpendicular to the x-axis. The simulation uses the Drude model fitted with the optical dielectric constant of Ag as the dielectric function. A perfectly matched layer is used as a periodic boundary condition along the x, y, and z axes. The mesh size is set to a constant value of 0.5nm.

[0076] For related performance tests, see Figure 5 , 6 、7.

[0077] Figure 5 (A) is the 10 nanoparticles collected on MXene, Ag NPs, Fe3O4@MXene, and Fe3O4@MXene@Ag NPs in Example 2.-5 M CV power Raman and SERS spectra, (B) CV collected on MXene (a), Fe3O4@MXene (b), Ag NPs (c), Fe3O4@MXene@Ag NPs (d) at 1617 cm -1 (C) is the proposed dual enhancement mechanism of the Fe3O4@MXene@Ag NPs composite substrate, (D) is the energy level diagram describing the CT process between the Fe3O4@MXene@Ag NPs composite substrate and CV, and (E) is the E field distribution diagram of the finite difference time domain (FDTD) simulation of MXene (left), Ag NPs (middle) and MXene@Ag NPs (right) substrates. Crystal violet (CV), a hazardous dye that poses a serious threat to the environment and human health, was selected as a probe molecule to study the detection performance of the dual-functional material. The CV powder sample is at 912 cm -1 、1170cm -1 、1370cm -1 、1588cm -1 and 1617cm -1 There are five key Raman peaks nearby. It is worth emphasizing that the peak at 1617 cm -1 The peak centered on shows an abnormal enhancement. Therefore, it was selected as the best peak for subsequent studies. It can be clearly seen that the unmodified MXene substrate has a significant chemical enhancement effect, and the enhancement factor (EF) corresponding to its SERS signal intensity is about 2.19×10 5 , which is significantly higher than the Raman signal of pure CV powder. Although the SERS intensity did not change significantly after composite with Fe3O4, the superparamagnetism of Fe3O4 nanoparticles facilitates magnetic separation. This ability reduces secondary contamination and provides a basis for the reusability of SERS substrates. In addition, the key role of MXene in enhancing SERS signals is further emphasized. Fe3O4@MXene@Ag NPs exhibited a stronger SERS signal with an EF value of 1.04×10 7 , which is significantly higher than the EF value of Ag NPs (5.91×10 6 ). Based on the band structures of CV and MXene, it was confirmed that 532nm laser (energy of 2.33eV) excitation can trigger two potential photoinduced charge transfer resonances (μPICT) of CV, as well as the molecular intrinsic resonance (μmol) occurring between the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) of CV. It is worth noting that the modified Ag NPs, due to their excellent conductivity, create an effective acceleration channel, promote the PICT process between MXene and CV, and ultimately enhance the SERS signal by amplifying the molecular polarization tensor.

[0078] This enhancement can be attributed to the gap-dependent plasmon coupling effect between the highly aggregated silver nanoparticles, and the local electromagnetic field distribution can be visualized by FDTD simulation. The near-field distribution associated with the MXene photoplasmonic system shows a strong electromagnetic field located at its edge with a maximum electric field intensity (Emax) of 2.72. The near-field distribution of the Ag NPs photoplasmonic system, a strong electromagnetic field with an Emax of 6.48 was observed around the spherical edge of the particles. When two Ag NPs were closely combined with MXene, the initially weak central region of the upper surface was significantly illuminated by an extremely strong electromagnetic field with an Emax of 11.70. This amplification of the electromagnetic field was partially attributed to the high dielectric constant of the MXene matrix, which significantly affected the oscillation frequency of the electrons on the surface of the Ag NPs. This coupling effect generates a stronger local electromagnetic field at the interface of MXene and Ag NPs than that of the surrounding bare Ag NPs. Therefore, enhanced SERS activity was observed in the MXene@Ag NPs composite substrate due to the chemically assisted electromagnetic effect. Theoretical simulation results confirmed that the MXene@Ag NPs composites formed more hotspots than Ag NPs or MXene alone, which is consistent with the experimental results and highlights the synergistic enhancement achieved by the combination.

[0079] Figure 6 (A) are different concentrations (1×10 -5 ~1×10 -11 M) SERS spectrum of CV on SERS substrate, (B) based on 1617 cm -1 Calibration curves of Raman intensity vs Log C [CV], the error bars represent the standard deviation determined by 3 independent measurements, (C) is a comparison of the linear range and LOD of CV detection of Fe3O4@MXene@AgNPs with other materials. -5 M and 10 -11 The increase between M will result in 1617cm -1 The peak intensity at the point increases linearly with the concentration, and the linear regression equation is I = 54546 + 4901.5log C (R 2 =0.995). The detection limit (LOD) was 1.08×10 -12 M. Comparison with previously reported SERS substrates showed that Fe3O4@MXene@AgNPs had a wider linear detection range and lower LOD than other materials.

[0080] Figure 7 (A) is a set of SERS spectra of 10 μM CV solution obtained from 20 random positions, and (B) is a 1617 cm -1(C) is the Raman intensity at 10 μM CV detected by Fe3O4@MXene@AgNPs, (D) is the quantitative result of CV SERS intensity in (C). Under the same conditions, we independently tested the CV sample solution (10 μM) in parallel at 20 different points. The RSD of SERS intensity in these parallel tests was 6.06%, which is acceptable for reproducibility. In order to verify the stability of the substrate we prepared, we tested Fe3O4@MXene@Ag NPs continuously for 1 month and detected 1617 cm in the SERS spectrum of CV. -1 The calculated intensity is 1617cm -1 The RSD of the Raman intensity at Figure 7 D). These RSD values ​​indicate reasonable stability, ensuring the practical applicability of Fe3O4@MXene@Ag NPs in real-world scenarios.

[0081] Example 3 Sensing mechanism of bifunctional Fe3O4@MXene@Ag NPs as photo-Fenton catalyst

[0082] Photo-Fenton degradation assay

[0083] The photo-Fenton degradation of CV by different catalysts was studied under 300W xenon lamp irradiation. In the experiment, 25mg of catalyst was uniformly dispersed in 100mL 10 -5 mol / L CV solution. The mixture was then placed in a dark environment and stirred continuously for 60 min to reach adsorption-desorption equilibrium. The photo-fenton process was started by adding 10 mM hydrogen peroxide (H2O2) and exposing the mixture to light irradiation. Throughout the process, 3 mL of the suspension sample was taken every 5 min and immediately filtered through a 0.22 μm membrane filter. The absorbance of these samples at 590 nm was measured using a UV-visible spectrophotometer to determine the remaining concentration of CV in the suspension. This procedure allows the degradation behavior of the catalyst to be evaluated under photo-fenton conditions.

[0084] For related performance tests, see Figure 8 , 9 、10.

[0085] Figure 8Figure 1 is the photo-Fenton degradation of CV on different samples (A) and the reaction kinetics (B); Figure 1 is the CV degradation (C) and reaction kinetics (D) of Fe3O4@MXene@Ag NPs under different conditions; experimental conditions: [CV]0 = 10 μM, [catalyst] = 250 mg / L, [H2O2] = 5 mM, pH (unadjusted). The removal efficiency of CV by Fe3O4 was 51.8% within 40 min. In contrast, Fe3O4@MXene showed a higher removal efficiency of 65.3% in the same period. This improvement suggests that the fixation of Fe3O4 on MXene nanosheets can improve the removal ability of CV. 2D MXene-based materials have excellent conductivity, numerous active sites and large surface area, which are conducive to the activation of H2O2, thereby improving the removal efficiency. Under the same conditions, Fe3O4@MXene@Ag NPs had the highest removal efficiency of 91.5%. The special effect of Fe3O4@MXene@Ag NPs in removing CV is mainly attributed to the enhanced photo-Fenton activity due to the Ag NPs modification. In addition, the photo-Fenton degradation of CV follows a pseudo-first-order kinetic model. In addition, we adjusted various influencing factors to determine their effects on CV degradation, focusing on the role of light and H2O2. Under light, the degradation efficiency of CV by Fe3O4 and Fe3O4@MXene was enhanced by 7% within 40 min. This enhancement suggests that light plays a catalytic role in the degradation of CV, which may be due to the photoinduced generation of electrons (e) when Fe3O4 is exposed to light. - ) and holes (h + ). In contrast, control experiments using only H2O2 under light conditions failed to achieve significant degradation of CV, emphasizing the critical role of catalysts in this process. This observation highlights the limitations of using H2O2 alone to effectively degrade CV and emphasizes the importance of catalysts such as Fe3O4 and Fe3O4@MXene in improving the photo-Fenton activity for degradation.

[0086] Fig. 9(A) and band gap energies (B) of Fe3O4, Fe3O4@MXene, and Fe3O4@MXene@Ag NPs; (C) are EIS graphs of Fe3O4@MXene and Fe3O4@MXene@Ag NPs. Compared with pure Fe3O4, the absorption edge of the composite material red-shifts after the introduction of MXene as a catalyst substrate. This indicates that the doping of MXene creates additional direct electron transfer channels, reducing the energy required for electrons in the composite photocatalyst to undergo hopping. Therefore, the light absorption capacity of the composite material is enhanced. In addition, the introduction of Ag NPs significantly enhances the light absorption capacity of Fe3O4@MXene in the visible light region. This enhancement is mainly attributed to the absorption and scattering of light by silver with good efficiency. This strong interaction occurs because the conduction electrons on the silver surface undergo collective oscillations when excited by light of a specific wavelength. This oscillation is called SPR, which leads to the absorption and scattering of light. The band gaps of Fe3O4, Fe3O4@MXene and Fe3O4@MXene@Ag NPs were calculated to be 2.47 eV, 2.30 eV and 1.90 eV, respectively, using the Kubelka-Munk formula. Fig. 9 B). The relatively narrow band gap of Fe3O4@MXene@Ag NPs is attributed to the strong interactions within the hybrid structure, which improves the utilization efficiency of the solar spectrum.

[0087] In electrochemical impedance spectroscopy, the smaller the arc radius of the Nyquist curve, the smaller the charge transfer resistance. Past studies have shown that integrating MXene into Fe3O4-based composites can effectively reduce the impedance radius due to the excellent conductivity of MXene. By comparing the impedance radii of Fe3O4@MXene and Fe3O4@MXene@Ag NPs, it was found that the addition of Ag NPs further reduced the impedance radius of Fe3O4@MXene. This observation suggests that Fe3O4@MXene@Ag NPs exhibit lower charge transfer resistance, resulting in faster interfacial charge transfer. The incorporation of Ag NPs enhances the separation of photogenerated electron-hole pairs inside Fe3O4. Based on the EIS results, it can be inferred that adding Ag NPs to Fe3O4@MXene is an effective strategy to improve the photocatalytic performance.

[0088] Fig.10 The effect of different scavengers on the CV removal efficiency of Fe3O4@MXene@Ag NPs (A), TEMPO-h + (B), DMPO-·O 2-In order to identify the active species produced in the catalytic reaction, we added isopropyl alcohol (IPA), ethylenediaminetetraacetic acid (EDTA-Na) and 1,4-benzoquinone (p-BQ) to quench ·OH, h + and O 2- . IPA, EDTA-Na and p-BQ inhibited the catalytic reaction. Under the optimal conditions, the degradation efficiency of Fe3O4@MXene@Ag NPs without any scavenger was 91.5%. In contrast, the photo-Fenton degradation activity decreased to 78.9%, 50.3% and 22.2% in the presence of EDTA-Na, IPA and p-BQ, respectively. The inhibition degree was p-BQ>IPA>EDTA-Na, indicating that ·OH and ·O 2- Free radicals are the main active species, and h + It is also the key active species for the photo-Fenton degradation of phenol by Fe3O4@MXene@Ag NPs. In addition, to verify the results of the scavenging experiments, time-dependent EPR measurements were performed using DMPO and TEMP as spin trapping agents. As the irradiation time increased, the EPR signal appeared spontaneously, indicating that the generation of ROS in the Fe3O4@MXene@AgNPs+H2O2 system must be light-dependent. After 5 minutes of irradiation, the TEMPO-h + DMPO-·O 2- and DMPO-·OH signals were consistent with the scavenging experiments.

[0089] Example 4 Stability and repeatability test of bifunctional Fe3O4@MXene@Ag NPs

[0090] Stability and repeatability testing

[0091] 10 -5 The CV of M was added to Fe3O4@MXene@Ag NPs, and then SERS detection was performed after natural drying. Then 5μL 5mM H2O2 was added, and then the detection was repeated, and then the detection was repeated. The alternating degradation was carried out in the same way, except that the detection substances were different.

[0092] Related data such as Fig.11 and Fig.12 .

[0093] Fig.11 Fe3O4@MXene@Ag NPs in 8 photo-Fenton system cycles -5 M CV SERS spectra (A) and 1617 cm -1(B) The peak intensity at 1617 cm-1 of Fe3O4@MXene@Ag NPs during 8 photo-Fenton system cycles. (C) The cyclic SERS detection of CV and R6G with different concentrations of dyes. (D) The CV of Fe3O4@MXene@Ag NPs during 8 photo-Fenton system cycles. -1 and R6G at 1648cm -1 To further elucidate the stability and reusability of Fe3O4@MXene@Ag NPs, sequential SERS detection and photo-Fenton degradation studies were performed on CV (10 μM) adsorbed on these NPs. After photo-Fenton treatment, the SERS peak of CV disappeared, but Fe3O4@MXene@Ag NPs maintained their commendable SERS activity over 8 cycles. The persistence of SERS intensity, especially at 1617 cm -1 The Fe3O4@MXene@Ag NPs almost completely maintained their SERS activity in the first three cycles. The slight decrease in the SERS signal after three cycles may be attributed to the slight loss of Fe3O4@MXene@Ag NPs or the decrease in adsorption capacity during the entire cycle process. It can be concluded that the proposed Fe3O4@MXene@Ag NPs have good recyclability and therefore have important prospects in the efficient detection and catalytic degradation of CV.

[0094] In addition, the reusability of the Fe3O4@MXene@Ag NPs substrate was further evaluated using different probe molecules. A 10μM CV solution was dropped onto Fe3O4@MXene@Ag NPs for SERS analysis and then degraded with H2O2 under simulated sunlight, resulting in a scenario where the SERS signal completely disappeared. Subsequently, a 10μM R6G solution was used for SERS detection and degradation on the Fe3O4@MXene@Ag NPs substrate, and then CV was applied again. This detection-cleaning cycle was performed 8 times. By monitoring the CV and R6G at 1617cm -1 and 1648cm -1 The sustained SERS activity of the Fe3O4@MXene@Ag NPs substrate was evaluated by the Raman signal intensity at 400 nm. The results confirmed that the SERS sensitivity of the Fe3O4@MXene@Ag NPs substrate remained almost unchanged during 8 detection and cleaning cycles, confirming the high stability and reusability of the substrate for different probe molecules.

[0095] Fig.12(A) is the degradation of Fe3O4@MXene@Ag NPs to CV in three cycles, (B) is the hysteresis loop of Fe3O4@MXene@Ag NPs measured at room temperature, (C) is the XPS spectra of fresh and used Fe3O4@MXene@Ag NPs catalysts, (D) is the Fe 2p high-resolution XPS spectra of fresh and used Fe3O4@MXene@Ag NPs catalysts, (E) is the XRD spectra of fresh and used Fe3O4@MXene@Ag NPs catalysts. The stability of Fe3O4@MXene@AgNPs in the photo-Fenton system was evaluated by CV degradation cycle experiments. After each cycle, the catalyst was separated from the solution by a magnet, washed and dried to prepare for the next cycle. The CV removal efficiency of the Fe3O4@MXene@Ag NPs system decreased from 91.5% to 80.9% in only 40 min after three rounds, indicating that the Fe3O4@MXene@Ag NPs maintained extremely high stability during the photo-Fenton process. Fig.12 (B) shows the hysteresis loop obtained by VSM measurement. The results show that the prepared material has typical superparamagnetism, with almost zero remanence and coercivity, and can be quickly separated from the dispersed solution under the action of an external magnetic field, indicating that it has sufficient magnetic properties. In addition, the excellent stable behavior of Fe3O4@MXene@Ag NPs can also be reflected from the XPS investigation and XRD patterns of fresh and used, with no significant differences in crystal structure and surface composition. Fig.12 (D) shows the Fe 2p XPS spectra of Fe3O4@MXene@Ag NPs before and after recycling. 2+ The content of Fe decreased slightly from 62.92% to 61.89%, while 3+ The content of Fe in Fe3O4@MXene@AgNPs increased from 37.08% to 38.11%. 2+ / Fe 3+ This indicates that during the photo-fenton reaction, a rapid Fe 2+ / Fe 3+ Redox cycle, thus maintaining Fe 2+ / Fe 3+ The high surface content of Fe3O4@MXene@Ag NPs facilitates the activation of H2O2 and facilitates the catalytic process. In addition, the XRD patterns of fresh and used samples demonstrate the excellent stability of Fe3O4@MXene@Ag NPs with minimal changes in their crystal structure. This consistency in the XRD spectra indicates that the composite retains its structural integrity even after repeated use, emphasizing its robustness for potential catalytic or sensing applications.

[0096] Example 5 The whole process of Fe3O4@MXene@Ag NPs in wastewater treatment

[0097] Preparation of actual samples

[0098] In the actual sample test of the present invention, laboratory tap water samples, river water from Hunhe River (Shenyang, China) and lake water from Dingxiang Lake (Shenyang, China) were used. In order to remove insoluble impurities, all water samples were pre-treated with a 0.22 μm syringe, and then CV solutions were prepared for detection and degradation tests.

[0099] For relevant data, see Fig.13 .

[0100] Fig.13 (A) is the geographical distribution and image of the sampling points, (B) is the schematic diagram of the sequential detection and cyclic detection process, and (C) is the dual-functional material in 10 -5 The sequential treatment of simulated sewage under M CV shows the step-by-step process of adsorption, detection and degradation, followed by the recovery and reuse of the material. Fe3O4@MXene@Ag NPs is an innovative bifunctional material with excellent SERS activity and photo-Fenton degradation ability for pollutants. The composite supports the sequential "detection then removal" treatment process of wastewater, promotes effective pollutant removal, and helps to mitigate environmental pollution. In order to evaluate the SERS detection and photo-Fenton degradation effects of Fe3O4@MXene@Ag NPs in actual water samples, CV detection and degradation experiments were performed on water samples from different locations. These samples included. First, the detection process was verified using laboratory tap water samples: 100mL 10 -5The M CV solution was mixed with 25 mg Fe3O4@MXene@Ag NPs for 60 min, and then 5 μL of the magnetic enrichment solution was extracted onto a glass slide and dried for SERS detection, showing a clear SERS signal. Photo-Fenton removal efficiency evaluation showed that the composite material could remove 90% of CV in tap water, and the SERS signal almost completely disappeared, confirming the excellent reusability of the substrate. The photo-Fenton treated material was then magnetically separated and cleaned, and then the same CV detection and removal procedures were performed in Hunhe River and Dingxiang Lake. The results showed that the SERS intensity of the three test scenarios was consistent. The Fe3O4@MXene@Ag NPs / visible light / H2O2 system achieved a removal efficiency of 86.7% for river water and 78.1% for sewage treatment plant effluent within 40 min. Compared with the control (ultrapure water), the degradation effect of the two real water samples decreased due to the presence of various complex inorganic ions and natural organic matter that interfered with the degradation of the target pollutants. Nevertheless, a CV removal efficiency of more than 75% was still achieved in both water matrices, which emphasizes the feasibility and potential of the Fe3O4@MXene@Ag NPs / visible light / H2O2 system in practical applications. In summary, this integrated technology not only achieves highly sensitive detection of pollutants, but also further purifies water through photo-Fenton degradation, significantly improving the efficiency and effectiveness of the water treatment process. This innovative technology platform opens up new avenues for applications in environmental monitoring and pollution control, with broad application prospects and potential social benefits.

Claims

1. A method for preparing bifunctional magnetic Fe3O4@MXene@Ag NPs with SERS and photo-Fenton catalytic activity, characterized in that: The steps include: 1) 100 mL of FeCl3·6H2O aqueous solution and 100 mL of FeCl2·4H2O aqueous solution were placed in a beaker, 1 mg / mL of MXene dispersion was added, and the mixture was stirred for 6 h. Then, 3 M NaOH solution was added to adjust the pH. The synthesis was continued for 2 h under mechanical stirring. A magnet was placed outside the beaker to make the nanosheets close to the inner surface of the beaker. The supernatant liquid was removed by pouring. Then, ethanol was added as a dispersant to the residual nanosheets, and the nanosheets were dispersed by oscillation. Then, the nanosheets were collected by magnetism and washed three times with ethanol to obtain Fe3O4@MXene nanosheets. 2) The Fe3O4@MXene nanosheets were dispersed in 5 mL of ethanol and ultrasonically treated for 20 min, then the Ag NPs solution was added and further ultrasonically treated for 4 h to ensure that the Ag NPs were loaded on the Fe3O4@MXene. Subsequently, the excess Ag NPs were removed by washing with water and ethanol, and the product was then dried to obtain Fe3O4@MXene@Ag NPs.

2. The preparation method according to claim 1, characterized in that: In step 1), the concentration of the FeCl3·6H2O aqueous solution is 0.030 mol / L, and the concentration of the FeCl2·4H2O aqueous solution is 0.015 mol / L.

3. The preparation method according to claim 1, characterized in that: In step 1), the pH is adjusted to 12.

4. The preparation method according to claim 1, characterized in that: In step 2), the amount of the Fe3O4@MXene nanosheets used is 0.05 g, and the amount of the Ag NPs solution used is 20 mL.

5. The preparation method according to claim 1, characterized in that: In step 1), the preparation method of the MXene dispersion comprises the following steps: 1) LiF was gradually added to the hydrochloric acid solution and stirred vigorously until the mixture changed from milky white to a transparent solution to form an acidic etching solution. Subsequently, Ti3AlC2 MAX phase powder was gradually added and stirred continuously at 35°C for 24 hours. After the reaction was completed, deionized water was added and centrifuged at 5000 rpm for 8 minutes. The supernatant was discarded and the deionized water washing and centrifugation cycle was repeated until the pH of the supernatant was close to 7. The black paste produced by centrifugation was freeze-dried to produce multilayer MXene nanosheets. 2) The multilayer MXene nanosheets were dispersed in DMSO and stirred continuously at 35 °C for 24 h. The mixture was then centrifuged at 8000 rpm for 5 min to remove DMSO. The remaining black paste was redispersed in 200 mL of deionized water and ultrasonically treated for 12 h to obtain a MXene dispersion with a concentration of 1 mg / mL.

6. The preparation method according to claim 5, characterized in that: In step 1), 1.6 g of LiF was gradually added to 20 mL of 9 M hydrochloric acid solution.

7. The preparation method according to claim 5, characterized in that: In step 1), the amount of Ti3AlC2 MAX phase powder added is 1 g.

8. The preparation method according to claim 5, characterized in that: In step 2), 0.2 g of multilayer MXene nanosheets was dispersed in 20 mL of DMSO.

9. The preparation method according to claim 1, characterized in that: In step 2), the method for preparing the Ag NPs solution comprises the following steps: 1) Prepare solution A and solution B: solution A is 100 mL of an aqueous solution containing 2 mM AgNO3, 0.4 M NH3OH and 0.5 mM CTAB, and solution B is 100 mL of an aqueous solution containing 8 mM NaBH4 and 0.5 mM CTAB; 2) Place solution A and solution B in an ice bath and cool for 10 minutes. Under vigorous stirring, drop solution B into solution A in the ice bath. Within 2 minutes, the solution turns yellow. Continue stirring in the dark for 3 hours. Subsequently, the particle dispersion is rapidly boiled, refluxed for 10 minutes, and then cooled to room temperature.

10. Application of the bifunctional magnetic Fe3O4@MXene@Ag NPs with SERS and photo-Fenton catalytic activity prepared by the preparation method according to any one of claims 1 to 9 in trace detection and photo-Fenton degradation of organic pollutants in sewage.

Citation Information

Cited By

  • Colorimetric-SERS (Surface Enhanced Raman Scattering) dual-mode nano enzyme sensor as well as preparation method and application thereof

    CN122193126A